Unilateral versus Bilateral Femoral Arterial Access for Uterine Artery Embolization - Ali, Hossam Mohsen Hassan Hussein; Abdel-Wahab, Sameh Mohamed; Abdel-Samad, Amr Mahmoud; El-Shimy, Ahmed (Open Access Macedonian Journal of Medical Sciences, 2022)
Background: Uterine fibroids are the most common benign tumors in women. Their clinical presentation includes menorrhagia, metrorrhagia, lower abdominal pain and infertility. Treatment of uterine fibroids includes medical management, surgical resection known as myomectomy as well as minimally invasive options like uterine artery embolization. Uterine artery embolization can be done via unilateral or bilateral femoral arterial access. We aim to define the differences between unilateral and bilateral femoral access in concern to radiation dose, procedure time , fluoroscopy time as well as the number of angiographic images. Methods: A total of 48 patients were divided into two groups equally; one with a unilateral femoral access and the other group with a bilateral femoral arterial access. Results: The age of the patients ranged between 25 to 40 years, embolization was done with calibrated spheres. Bilateral procedures compared to the unilateral ones had less fluoroscopy times (8.6 minutes vs 24.3 mins) , less total procedure time (28.4 minutes vs 54.4 minutes) and less dose area product (155 Gy cm2 vs 340.5 Gy cm2) as well as less mean number of angiographic images (93.8 vs 176.5) with no significant difference in puncture site complications. Conclusion: Fluoroscopy times, procedure times, number of angiographic images as well as radiation dose were significantly lower in the bilateral approach with no significant difference in the rates of puncture site complications between the two approaches. Keywords: Uterine Artery Embolization, uterine fibroids, unilateral versus bilateral access.